2022
DOI: 10.15448/1980-8623.2022.1.36703
|View full text |Cite
|
Sign up to set email alerts
|

Bem-estar psicológico, sintomas de depressão e forças do caráter em idosos da comunidade

Abstract: Em um mundo com um número crescente de idosos, envelhecer bem se torna cada vez mais importante, e as forças do caráter podem contribuir para que isso seja alcançado. A fim de analisar forças na velhice, associando-as com sintomas depressivos e bem-estar psicológico, 188 idosos responderam às versões reduzidas e em português dos instrumentos Values-in-Action Inventory of Strengths, Escala de Depressão Geriátrica e Philadelphia Geriatric Center Morale Scale. As forças Amor, Esperança, Curiosidade, Perdão e Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…However, when investigating young high school students, Niemiec (2017) observed that the association was with love, self-regulation, hope, and gratitude, in addition to citizenship predicting depression. Finally, in the study by Freitas and Barbosa (2022), with an elderly population, enables the individual to recognize, rejoice and be grateful both for the good things that happen in life, as well as for the people who help to make it happen, we believe that this trait provides support for the teacher to be able to maintain interpersonal relationships and deal with challenges at work in a "lighter" and healthier way -contributing to not getting sick. The same can be said of hope, since the optimism generated by it makes the subject experience more positive affects and less negative ones.…”
Section: Eyes On Health Sciences V02mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when investigating young high school students, Niemiec (2017) observed that the association was with love, self-regulation, hope, and gratitude, in addition to citizenship predicting depression. Finally, in the study by Freitas and Barbosa (2022), with an elderly population, enables the individual to recognize, rejoice and be grateful both for the good things that happen in life, as well as for the people who help to make it happen, we believe that this trait provides support for the teacher to be able to maintain interpersonal relationships and deal with challenges at work in a "lighter" and healthier way -contributing to not getting sick. The same can be said of hope, since the optimism generated by it makes the subject experience more positive affects and less negative ones.…”
Section: Eyes On Health Sciences V02mentioning
confidence: 99%
“…Although in Positive Psychology life satisfaction and well-being are the constructs commonly used for the conceptualization and measurement of mental health, researchers in this line of thought have paid attention to the importance of investigating the relationship of character strengths with various variables that directly or indirectly influence people's quality of life (Chan, 2013;Freitas & Barbosa, 2022;Lian et al, 2021;Noronha & Batista, 2020). Thus, understanding that the panorama presented at the beginning of the chapter should be similar to the reality of teachers in other countries, the incidence of psychopathologies in teachers was also a field of research interest.…”
Section: The Role Of Character Strengths In Teacher Mental Healthmentioning
confidence: 99%
“…Uma prática comum, seria a prática isomórfica, ou seja, o espelhamento dos gestos praticados pelo corpo humano, como exemplo, copiar a linguagem corporal do outro, se a outra pessoa cruza os braços, cruzamos os nossos, podendo gerar um conforto ou inquietação no outro, e até mesmo ganhando sua atenção (FREITAS, 2022).…”
Section: Influência Sinais De Que O Corpo E a Mente Nos Revelamunclassified
“…Um simples gesto pode nos mostrar muito, como um simples sorriso, como um sinal amistoso (FREITAS, 2022).…”
Section: Caminhos Da Ciência: Uma Visão Das áReas Do Conhecimentounclassified